O entrelaçamento dialético entre Mito e Aufklärung no primeiro capítulo da Dialética do esclarecimento de Adorno e Horkheimer - Moreira, Sérgio Augusto (2012)
"Interweaving the dialectic between myth and Aufklärung in the first chapter of the dialectics of Enlightenment, Adorno and Horkheimer" (Sérgio Augusto Moreira). The theme of this research shows the meanders dialectic that are opposite and complementary between myth and Aufklärung, in which points to the dimension of domination of nature in the historical context of western reason since epic Penelope's tapestry until the Enlightenment. Meanwhile, another dimension permeates within this issue of domination of nature: the salvage of emancipation of subject contemporary and, within this dimension that is born the urgency of emancipating the subject, to rescue the broken subject in itself. The emancipation of the subject broken only happens with the recognition of the warp systematic domination existing in social life, searching for means of abstraction, protrude of intermittent sufferings of current reality, feeling the blow of autonomy gradually growing in awareness of the subject